Optimalisasi Sarana dan Prasarana untuk Mendukung Proses Pembelajaran - Asyifah Luthfiyah; Najwa Azzahra; Ahmad Alghifari; Hesti Kusumaningrum (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the process of management of educational facilities and infrastructure in an effort to improve the quality of education in elementary schools. Facilities and infrastructure have an important role in education, and the existence of adequate facilities can help improve the quality of learning. This study uses a descriptive qualitative method, with data sources obtained through observation, interviews, and documentation. Interview informants include school principals, teachers who manage facilities and infrastructure, and subject teachers. The results of the study show that school facilities and infrastructure are well managed, including planning, procurement, use, inventory, removal, and supervision. The management process runs smoothly, which makes stakeholders feel satisfied and contributes to achievements.